The Effect Of Herbal Toothpaste With Siwak Extract On The Tensile Force Of Orthodontic Elastomer Power Chain Elastomers - Savira, Nabila Sarah; Eriwati, Yosi Kusuma; Herda, Ellyza (FKG Universitas Syiah Kuala, 2025)
Power chains elastomers are one of the most commonly used devices in orthodontic treatment. Recently, herbal toothpastes containing siwak extract has been developed, which shown to be more effective in reducing plaque index compared to non-herbal toothpastes. However, siwak extract contains fluoride that may reduce tensile force. This study aimed to analize the effect of herbal siwak toothpaste and non-herbal toothpaste on the tensile force of orthodontic power chains elastomers. A total of 144 power chain elastomer specimens were immersed in treatment groups,Aquadest and Pepsodent Complete 8 Siwak toothpaste solution, Aquadest and Pepsodent toothpaste solution, and Aquadest as the control group. The tensile force of the power chain elastomer was measured using a Universal Testing Machine (UTM) after immersion for 6, 42, 84, 126, and 168 minutes. The data were analyzed using one way ANOVA test. The result showed that after the immersion, the tensile force of power chain elastomers in aquadest, non-herbal toothpaste, and herbal siwak toothpaste were significantly different (p0,05). Herbal siwak toothpaste caused a smaller reduction in the tensile force of the orthodontic power chain elastomers compared to non-herbal toothpaste. It can be concluded that immersion in herbal siwak toothpaste results in a greater reduction in tensile force compared to the control group, which was immersed in Aquadest.